Sex role socialization and perceptions of student academic dishonesty by male and female accounting faculty. (2nd January 2018) - Lento, Camillo; Sayed, Naqi; Bujaki, Merridee
ABSTRACT: We examine differences between male and female accounting faculty members' perceptions of academic dishonesty and their uses of controls to prevent academically dishonest behaviour. We use socialization concepts to motivate our examination of these differences. Specifically, we find that females generally perceive academic dishonesty to be a more significant problem than do males, females see individual incidences of academic dishonesty as more frequent and more significant than do males, and female academics report they exercise controls to prevent academic dishonesty more frequently than do male academics. These findings are consistent with differential sex role socialization for women and men. We also find that male and female accounting academics' perceptions converge with professional training and teaching experience, suggesting moderating impacts of professional and/or organizational socialization on perceptions of academic dishonesty. Lastly, we document some differences in how male and female accounting academics respond to known incidences of academically dishonest behaviour.